Profil épidémiologique des maladies cardiovasculaires dans la Ville de Meknès (Maroc) - Ibrahim El Ghazi; Imane Berni; Aziza Menouni; Marie-Paule Kestemont; Mohammed Amane; Samir El Jaafari (European Scientific Journal, ESJ, 2018)
Introduction: In Morocco, very little published work has focused on cardiovascular diseases. As a result, the main objective of this research is to evaluate the epidemiological profile of cardiovascular diseases in patients who are hospitalized and treated in the cardiology department of Mohammed V Hospital, Meknes (Morocco). Methods: This is a retrospective descriptive and analytical study of 1112 patients admitted to this department over a fouryear period (from January 1, 2011 to December 31, 2014). Results: 54.49 % of patients were women and the most affected age group was 45-64 years old (42.08 %) (p < 0.001). The most common pathologies among hospitalized patients were: ischemic heart disease which represented the first cause of hospitalization with 341 cases corresponding to 30.66 %, followed by heart failure (20.59 %). Ischemic heart disease was more common in men (p = 0.05) while women were more affected by high blood pressure (p = 0.0096), heart failure (p = 0.06) and venous thrombosis (p < 0.05). Conclusion: Cardiovascular pathologies represent a real health and socio-economic problem for families and health facilities. The frequency and severity of these diseases should prompt us to do further research on this topic to find the most plausible solutions to reduce negative impacts.